2022
DOI: 10.1021/acsami.2c12537
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Core–Shell-Structured Nanofiber Membranes for Rapid and Portable Water Purification

Abstract: Rapid and portable water purification (RPWP) technologies, helping travelers survive in the wild, have attracted increasing interest due to increasing activities, such as exploration, field hiking, and excursion. Field water is usually pathogenic because of various soluble and insoluble contaminants. In this study, fish-gilllike biomimetic core−shell-structured nanofiber membranes are designed and synthesized by an in situ oxidation polymerization coating process. A polyimide nanofiber membrane and a polypyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The optical photos of the synthetic PPy@Al 2 O 3 ceramic fiber fabric are shown in Figure c, in which the ceramic fiber fabric in Figure c (1–4) was Al 2 O 3 , PPy@Al 2 O 3 -10, PPy@Al 2 O 3 -20, and PPy@Al 2 O 3 -40 successively. The initial white Al 2 O 3 ceramic fiber fabric turned black during in situ oxidative polymerization, indicating the formation of black polypyrrole on the original Al 2 O 3 ceramic fiber Figure d shows the images of PPy@Al 2 O 3 -20 ceramic fiber fabric before and after synthesis, which can be scaled up for production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical photos of the synthetic PPy@Al 2 O 3 ceramic fiber fabric are shown in Figure c, in which the ceramic fiber fabric in Figure c (1–4) was Al 2 O 3 , PPy@Al 2 O 3 -10, PPy@Al 2 O 3 -20, and PPy@Al 2 O 3 -40 successively. The initial white Al 2 O 3 ceramic fiber fabric turned black during in situ oxidative polymerization, indicating the formation of black polypyrrole on the original Al 2 O 3 ceramic fiber Figure d shows the images of PPy@Al 2 O 3 -20 ceramic fiber fabric before and after synthesis, which can be scaled up for production.…”
Section: Resultsmentioning
confidence: 99%
“…The initial white Al 2 O 3 ceramic fiber fabric turned black during in situ oxidative polymerization, indicating the formation of black polypyrrole on the original Al 2 O 3 ceramic fiber. 34 Figure 1d shows the images of PPy@Al 2 O 3 -20 ceramic fiber fabric before and after synthesis, which can be scaled up for production. At the same time, one of the very important properties of textiles is their cutability and bendability; Figure S1a shows that the PPy@ Al 2 O 3 ceramic fiber fabric can be cut into complex patterns, and Figure S1b,c shows that it can be bent to varying degrees.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results confirmed that the adsorption process followed a pseudo-second-order model, suggesting that the adsorption mechanism is mainly controlled by chemical absorption, which can be associated to ion-ion interactions between the MB and CNC-HNT-0.4 aerogel. 55 Fig. 4 Effect of CNC-HNT-0.4 dosages on the adsorption capacity (A) and removal efficiency of MB (B).…”
Section: Adsorption Kinetics and Mechanismmentioning
confidence: 99%
“…[1] As a result, solving the freshwater DOI: 10.1002/smll.202311731 problem becomes the first difficulty in the adventure process, especially in the extremely harsh scenarios such as seawaterdominated island, bacterial river waterdominated forest and waterless desert. [2] Therefore, many explorers are often in danger of dying due to extreme dehydration or drinking contaminated water. [3] Currently, many explorers solve freshwater problem mainly through filtration purification, cooking condensation and direct solar evaporation to purify seawater, bacterial river water and collected urine, but such methods are usually inefficient and laborious.…”
Section: Introductionmentioning
confidence: 99%